A CASE STUDY OF HOW SPEAKING SKILL TAUGHT TO EFL STUDENTS IN JUNIOR HIGH SCHOOL LEVEL - Abdul Ghafur; Siti Maria Ulfa (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
Speaking is again can be seen as a skill which is very difficult to be taught, learnt and observed. Since its urgency in making meaningful communication between students, this research is conducted within the pandemic situation. Mostly teachers are reluctant even left the students with their own speaking ability without any constructive ideas or strategies to overcome this crucial problems. The researcher’s taught is blowing with tis condition and it is important to investigate the phenomena of how speaking skill taught especially in Junior High School moreover within this new normal era. With its all limitation, this research focus on only to see how the teacher teaches students in term of speaking skill. The method of this research is qualitative that observation and interpretation are mostly used to obtain the data for detailed results and discussion. The observation is done to see the real phenomena happened within the classroom while the teaching and learning process is running, and there is no any intervention from the researcher at all. While the interpretation is done to reveal the condition how is actually the speaking skill is taught following minimum standard of how actually speaking skill be given in Junior High School level. The results and discussion have shown that the teacher implements collaborative work and maximize the feedback to improve students’ exposure to certain spoken language from them. However, this kind of finding is yet constructively help students with their speaking. It still needs a lot of adequate strategies to explore the students’ speaking skill to the fullest.